Maxillary Sinus Floor Augmentation Using an Equine-Derived Graft Material: Preliminary Results in 17 Patients. (25th October 2017) - Rivara, F.; Negri, M.; Lumetti, S.; Parisi, L.; Toffoli, A.; Calciolari, E.; Manfredi, E.; Macaluso, G. M.
Abstract : Objective . Sinus floor elevation with lateral approach is probably the most frequently performed reconstructive procedure to rehabilitate posterior maxilla when a bone deficiency is present. Different graft materials have been proposed and tested, often with high clinical performances and predictable results. Histological analysis is required when evaluating new materials. We investigated human biopsies retrieved after sinus floor elevation procedure by histomorphometric evaluation to test the performance of an equine-derived bone grafting material. Study Design . Seventeen consecutive patients were enrolled and sinus lift surgeries were performed using an equine bone graft. Six months after surgery, at implant placement, bone samples were collected. Histomorphometry analysis was carried out on decalcified samples. Results . All surgeries were uneventful and no additional grafting was required prior to implant insertion. Forty percent of new bone formation was detected, which represented the most abundant tissue retrieved, followed by the residual graft material (33%) and fibrous tissue (27%). A significant reduction in particles size demonstrates a remodeling activity of the graft material. Conclusion . Within the limitations of this study, this equine-derived bone graft proved to be an effective material to induce new bone formation in the sinus floor elevation procedure.